Liquid metal-manganese oxide-MXene wave-absorbing phase-change composite particle as well as preparation method and application thereof
Through the unique three-layer structure of liquid metal-manganese oxide-MXene wave absorption phase change composite particles, the impedance matching and absorption bandwidth problems of existing electromagnetic wave absorption materials are solved, and efficient electromagnetic wave absorption and phase change heat absorption cooling are achieved. Application in multiple fields.
Patent Information
- Application Number
- CN202411340168.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-17
AI Technical Summary
The existing electromagnetic wave absorption materials have poor impedance matching, narrow electromagnetic absorption bandwidth, large matching thickness and single functions, which are difficult to meet the practical application requirements.
Liquid metal-manganese oxide-MXene wave absorbing phase transformation composite particles are used, which consists of liquid metal core, manganese oxide intermediate shell and MXene outer cladding layer. Through specific component ratios and preparation methods, impedance matching and Multiple interface polarization losses improve electromagnetic wave absorption performance.
It realizes excellent electromagnetic wave absorption performance and phase change heat absorption and cooling function, with a small matching thickness, and is suitable for 5G communications, consumer electronics and defense and military industries.
Smart Images

Figure CN119144283A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electromagnetic protection technology, and in particular to a liquid metal-manganese oxide-MXene wave-absorbing phase-change composite particle and a preparation method and application thereof. Background Art
[0002] With the rapid development of science and technology, people use a large number of consumer electronic products and electronic components in their daily lives and industrial production processes. These products and components may face abnormal equipment operation caused by electromagnetic wave radiation interference during operation, and electromagnetic radiation pollution may also cause potential harm to human health. In order to solve the above-mentioned electromagnetic interference and electromagnetic radiation pollution problems, the development and application of various high-performance electromagnetic wave absorbing materials are becoming more and more urgent. However, existing electromagnetic wave absorbing materials generally have problems such as poor impedance matching, narrow electromagnetic absorption bandwidth, large matching thickness, and relatively single function, which makes it difficult to fully meet the requirements of actual applications.
[0003] Therefore, it is of great significance to develop a high-performance electromagnetic wave absorption material with high absorption intensity, wide absorption bandwidth, small matching thickness and diverse functions. Summary of the invention
[0004] The object of the present invention is to provide a liquid metal-manganese oxide-MXene wave absorbing phase change composite particle and a preparation method and application thereof.
[0005] The technical solution adopted by the present invention is:
[0006] A liquid metal-manganese oxide-MXene wave-absorbing phase-change composite particle, which comprises a liquid metal inner core, a manganese oxide intermediate shell layer and a MXene outer coating layer.
[0007] Preferably, the liquid metal-manganese oxide-MXene wave absorbing phase change composite particles include the following components in percentage by mass:
[0008] Liquid metal: 57%~88%;
[0009] Manganese oxide: 4% to 26%;
[0010] MXene: 5% to 16%;
[0011] Surfactant: 0.1%~1%.
[0012] Further preferably, the liquid metal-manganese oxide-MXene absorbing phase change composite particles include the following components in percentage by mass:
[0013] Liquid metal: 75% to 88%;
[0014] Manganese oxide: 5% to 15%;
[0015] MXene: 5% to 16%;
[0016] Surfactant: 0.4%~0.8%.
[0017] Preferably, the liquid metal is at least one of elemental gallium, gallium-indium alloy, gallium-indium-tin alloy, and gallium-zinc alloy.
[0018] Preferably, the manganese oxide is at least one of manganese dioxide, trimanganese tetroxide and dimanganese trioxide.
[0019] Preferably, the MXene is at least one of titanium carbide MXene, manganese carbide MXene, and zirconium carbide MXene.
[0020] Preferably, the surfactant is at least one of polyvinyl pyrrolidone, cetyl trimethyl ammonium bromide, cetyl trimethyl ammonium chloride and cetyl pyridine.
[0021] A method for preparing the liquid metal-manganese oxide-MXene wave absorbing phase change composite particles as described above comprises the following steps:
[0022] 1) dispersing liquid metal and surfactant in water to prepare a liquid metal dispersion, then adding the dispersion into a potassium permanganate solution for reaction, and then separating and purifying the product to obtain liquid metal-manganese oxide composite particles;
[0023] 2) dispersing the liquid metal-manganese oxide composite particles and the surfactant in water to perform surface modification of the liquid metal-manganese oxide composite particles, and then separating and purifying the products to obtain surface-modified liquid metal-manganese oxide composite particles;
[0024] 3) Dispersing MXene in water to prepare a MXene dispersion, then adding the surface-modified liquid metal-manganese oxide composite particles into the MXene dispersion to electrostatically adsorb and coat the MXene on the surface of the surface-modified liquid metal-manganese oxide composite particles, and then separating and purifying the products to obtain liquid metal-manganese oxide-MXene absorbing phase change composite particles.
[0025] Preferably, a method for preparing the liquid metal-manganese oxide-MXene absorbing phase change composite particles as described above comprises the following steps:
[0026] 1) dispersing liquid metal and surfactant in water to prepare liquid metal dispersion, adding the dispersion into potassium permanganate solution for reaction, centrifuging and washing the product, and freeze-drying the product to obtain liquid metal-manganese oxide composite particles;
[0027] 2) dispersing the liquid metal-manganese oxide composite particles and the surfactant in water to modify the surface of the liquid metal-manganese oxide composite particles, and then centrifuging and washing the product to obtain surface-modified liquid metal-manganese oxide composite particles;
[0028] 3) Dispersing MXene in water to prepare a MXene dispersion, then adding the surface-modified liquid metal-manganese oxide composite particles into the MXene dispersion to electrostatically adsorb and coat the surface of the surface-modified liquid metal-manganese oxide composite particles, then centrifuging the product, and then freeze-drying it to obtain liquid metal-manganese oxide-MXene absorbing phase change composite particles.
[0029] Preferably, the dispersion in step 1) is ultrasonic dispersion, the ultrasonic power is 200W to 400W, and the ultrasonic time is 3min to 30min.
[0030] Preferably, in step 1), the mass ratio of the liquid metal, surfactant and water is 1:0.05-0.15:10-30.
[0031] Preferably, in step 1), the mass ratio of the liquid metal to potassium permanganate is 1:0.10-0.63.
[0032] Preferably, the reaction in step 1) is carried out at room temperature, and the reaction time is 10 min to 60 min.
[0033] Preferably, the reaction in step 1) is carried out under stirring at a speed of 400 rpm to 1500 rpm.
[0034] Preferably, the centrifugation in step 1) is carried out at a centrifuge speed of 2000 rpm to 3500 rpm, and the centrifugation time is 3 min to 10 min.
[0035] Preferably, the freeze-drying in step 1) is carried out at a temperature of -50°C to -70°C, and the drying time is 12h to 24h.
[0036] Preferably, in step 2), the mass ratio of the liquid metal-manganese oxide composite particles, surfactant and water is 1:0.10-0.25:60-120.
[0037] Preferably, the dispersion in step 2) is ultrasonic dispersion, the ultrasonic power is 250W to 500W, and the ultrasonic time is 30min to 60min.
[0038] Preferably, the centrifugation in step 2) is carried out at a centrifuge speed of 2000 rpm to 3500 rpm, and the centrifugation time is 3 min to 10 min.
[0039] Preferably, in step 3), the mass ratio of the MXene to water is 1:200 to 2400.
[0040] Preferably, in step 3), the mass ratio of the surface modified liquid metal-manganese oxide composite particles to MXene is 1:0.05-0.20.
[0041] Preferably, the dispersion in step 3) is ultrasonic dispersion, the ultrasonic power is 250W to 500W, and the ultrasonic time is 30min to 90min.
[0042] Preferably, the electrostatic adsorption coating in step 3) is carried out at room temperature for 6 hours to 12 hours.
[0043] Preferably, the electrostatic adsorption coating in step 3) is carried out under stirring at a stirring speed of 400 rpm to 1500 rpm.
[0044] Preferably, the centrifugation in step 3) is carried out at a centrifuge speed of 2000 rpm to 3500 rpm, and the centrifugation time is 3 min to 10 min.
[0045] Preferably, the freeze-drying in step 3) is carried out at a temperature of -50°C to -70°C, and the drying time is 12h to 24h.
[0046] An application of the liquid metal-manganese oxide-MXene absorbing phase change composite particles as described above in the fields of 5G communications, consumer electronics or national defense and military industry.
[0047] The beneficial effects of the present invention are: the liquid metal-manganese oxide-MXene absorbing phase change composite particles of the present invention have excellent electromagnetic wave absorption performance, and also have phase change heat absorption and cooling function, and have a small matching thickness and a simple preparation method, and are suitable for 5G communications, consumer electronics, national defense and military industries and other fields.
[0048] Specifically:
[0049] 1) The liquid metal-manganese oxide-MXene absorbing phase change composite particles of the present invention have a unique three-layer core-shell structure (i.e., liquid metal as the core, manganese oxide as the middle shell, and MXene as the outer coating layer), which can effectively adjust the electromagnetic parameters of the composite particles to achieve impedance matching. At the same time, the three-layer core-shell structure has dielectric loss, conductive loss, and multiple interface polarization loss mechanisms, so that the composite particles have excellent absorbing performance;
[0050] 2) The present invention uses a complete manganese oxide shell to coat the liquid metal, which solves the problem of easy leakage and surface oxidation of the liquid metal. The liquid metal has the characteristic of high volume phase change latent heat, which gives the composite particles a phase change heat absorption and cooling function, and can play a good thermal conductivity and heat dissipation effect. At the same time, since manganese oxide is a dielectric material, it can effectively improve the impedance mismatch between the liquid metal and MXene due to high dielectric constant, enhance the interface polarization effect, and thus improve the electromagnetic wave absorption performance of the composite particles;
[0051] 3) The reaction between the liquid metal and potassium permanganate in the present invention is mild (the liquid metal and potassium permanganate undergo an galvanic replacement reaction at the interface between the two), which can proceed spontaneously at room temperature, and the reaction does not require high temperature, which can effectively avoid the oxidation of MXene;
[0052] 4) The preparation method of the liquid metal-manganese oxide-MXene absorbing phase change composite particles of the present invention is simple, green and environmentally friendly throughout the process, and is suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is a SEM image of the gallium indium tin alloy particles in the gallium indium tin alloy dispersion in Example 2.
[0054] Figure 2 This is a SEM image of the gallium indium tin alloy-manganese dioxide composite particles in Example 2.
[0055] Figure 3 This is the SEM image of the gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particles in Example 2.
[0056] Figure 4 This is the reflection loss curve of the coaxial ring sample versus frequency. DETAILED DESCRIPTION
[0057] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0058] Embodiment 1:
[0059] A gallium indium tin alloy-manganese dioxide-titanium carbide MXene wave absorbing phase change composite particle, which is composed of a gallium indium tin alloy core, a manganese dioxide intermediate shell layer and a titanium carbide MXene outer coating layer. The specific components and contents are shown in the following table:
[0060] Table 1 Composition of a gallium indium tin alloy-manganese dioxide-titanium carbide MXene microwave absorbing phase change composite particle
[0061]
[0062]
[0063] The preparation method of the above-mentioned gallium indium tin alloy-manganese dioxide-titanium carbide MXene wave absorbing phase change composite particles is as follows:
[0064] 1) Polyvinyl pyrrolidone (PVP-K30) was dispersed in deionized water, and then the gallium indium tin alloy was added and intermittent ultrasonic dispersion was performed using an ultrasonic cell disruptor (ultrasonication for 2s, intermittent for 2s, and this cycle was repeated). The ultrasonic power was 200W, the ultrasonic dispersion time was 10min, and the mass ratio of gallium indium tin alloy, polyvinyl pyrrolidone, and deionized water was 1:0.1:20 to obtain a gallium indium tin alloy dispersion; potassium permanganate was added to the deionized water, and the mass ratio of potassium permanganate to deionized water was 1 :1600, mechanically stirred for 5 minutes at a stirring speed of 500 rpm, then added gallium indium tin alloy dispersion, the mass ratio of potassium permanganate to gallium indium tin alloy was 0.13:1, mechanically stirred for 30 minutes at a stirring speed of 500 rpm, then the product was alternately centrifuged 3 times and washed with water 3 times, the speed of the centrifuge was 2000 rpm, the time of a single centrifugation was 5 minutes, and then the solid obtained by centrifugation was freeze-dried at -50°C for 12 hours to obtain gallium indium tin alloy-manganese dioxide composite particles;
[0065] 2) adding the gallium indium tin alloy-manganese dioxide composite particles to a hexadecyltrimethylammonium bromide aqueous solution, wherein the mass ratio of the gallium indium tin alloy-manganese dioxide composite particles, the hexadecyltrimethylammonium bromide, and water is 1:0.2:100, and then ultrasonically dispersing for 60 minutes, the ultrasonic power is 250 W, and then the product is alternately centrifuged 3 times and washed 3 times, the speed of the centrifuge is 2000 rpm, and the single centrifugation time is 5 minutes, to obtain surface-modified gallium indium tin alloy-manganese dioxide composite particles;
[0066] 3) Add titanium carbide MXene to deionized water, ultrasonically disperse for 60 minutes, the ultrasonic power is 250 W, and then add surface modified gallium indium tin alloy-manganese dioxide composite particles, the mass ratio of surface modified gallium indium tin alloy-manganese dioxide composite particles, titanium carbide MXene, and deionized water is 1:0.2:100, mechanically stir for 10 hours, the stirring speed is 500 rpm, centrifuge for 5 minutes, the speed of the centrifuge is 2000 rpm, and then the solid obtained by centrifugation is placed at -50°C and freeze-dried for 24 hours to obtain gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particles.
[0067] Embodiment 2:
[0068] A gallium indium tin alloy-manganese dioxide-titanium carbide MXene wave absorbing phase change composite particle, which is composed of a gallium indium tin alloy core, a manganese dioxide intermediate shell layer and a titanium carbide MXene outer coating layer. The specific components and contents are shown in the following table:
[0069] Table 2 Composition of a gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particle
[0070] Components Mass percentage (%) Gallium indium tin alloy (same as Example 1) 84.7 Manganese dioxide 6.2 Titanium Carbide MXene 8.5 Polyvinylpyrrolidone 0.3 Hexadecyltrimethylammonium bromide 0.3
[0071] The preparation method of the above-mentioned gallium indium tin alloy-manganese dioxide-titanium carbide MXene wave absorbing phase change composite particles is as follows:
[0072] 1) Polyvinyl pyrrolidone (PVP-K30) was dispersed in deionized water, and then the gallium indium tin alloy was added and intermittent ultrasonic dispersion was performed using an ultrasonic cell disruptor (ultrasonication for 2s, intermittent for 2s, and this cycle was repeated). The ultrasonic power was 200W, the ultrasonic dispersion time was 10min, and the mass ratio of gallium indium tin alloy, polyvinyl pyrrolidone, and deionized water was 1:0.1:20 to obtain a gallium indium tin alloy dispersion; potassium permanganate was added to the deionized water, and the mass ratio of potassium permanganate to deionized water was 1 :1600, mechanically stirred for 5 minutes at a stirring speed of 500 rpm, then added gallium indium tin alloy dispersion, the mass ratio of potassium permanganate to gallium indium tin alloy was 0.13:1, mechanically stirred for 30 minutes at a stirring speed of 500 rpm, then the product was alternately centrifuged 3 times and washed with water 3 times, the speed of the centrifuge was 2000 rpm, the time of a single centrifugation was 5 minutes, and then the solid obtained by centrifugation was freeze-dried at -50°C for 12 hours to obtain gallium indium tin alloy-manganese dioxide composite particles;
[0073] 2) adding the gallium indium tin alloy-manganese dioxide composite particles to a hexadecyltrimethylammonium bromide aqueous solution, wherein the mass ratio of the gallium indium tin alloy-manganese dioxide composite particles, the hexadecyltrimethylammonium bromide, and water is 1:0.2:100, and then ultrasonically dispersing for 60 minutes, the ultrasonic power is 250 W, and then the product is alternately centrifuged 3 times and washed 3 times, the speed of the centrifuge is 2000 rpm, and the single centrifugation time is 5 minutes, to obtain surface-modified gallium indium tin alloy-manganese dioxide composite particles;
[0074] 3) Add titanium carbide MXene to deionized water, ultrasonically disperse for 60 minutes, the ultrasonic power is 250 W, and then add surface modified gallium indium tin alloy-manganese dioxide composite particles, the mass ratio of surface modified gallium indium tin alloy-manganese dioxide composite particles, titanium carbide MXene, and deionized water is 1:0.1:100, mechanically stir for 10 hours, the stirring speed is 500 rpm, centrifuge for 5 minutes, the speed of the centrifuge is 2000 rpm, and then the solid obtained by centrifugation is placed at -50°C and freeze-dried for 24 hours to obtain gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particles.
[0075] Performance Test:
[0076] The scanning electron microscope (SEM) image of the gallium indium tin alloy particles in the gallium indium tin alloy dispersion in this embodiment is as follows: Figure 1 As shown, the SEM image of the gallium indium tin alloy-manganese dioxide composite particles is as follows Figure 2 As shown, the SEM image of the GaInSn alloy-manganese dioxide-titanium carbide MXene microwave absorbing phase change composite particles is shown in Figure 3 shown.
[0077] Depend on Figure 1 and Figure 2 It can be seen that the surfaces of the gallium indium tin alloy particles and the gallium indium tin alloy-manganese dioxide composite particles are relatively smooth, and the manganese dioxide shell layer on the surface of the gallium indium tin alloy-manganese dioxide composite particles is relatively complete.
[0078] Depend on Figure 3 It can be seen that the surface of the gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particles is rough, and titanium carbide MXene with larger flakes is attached to the surface of the composite particles.
[0079] Embodiment 3:
[0080] A gallium indium tin alloy-manganese dioxide-titanium carbide MXene wave absorbing phase change composite particle, which is composed of a gallium indium tin alloy core, a manganese dioxide intermediate shell layer and a titanium carbide MXene outer coating layer. The specific components and contents are shown in the following table:
[0081] Table 3 Composition of a gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particle
[0082] Components Mass percentage (%) Gallium indium tin alloy (same as Example 1) 87.2 Manganese dioxide 6.4 Titanium Carbide MXene 5.8 Polyvinylpyrrolidone 0.3 Hexadecyltrimethylammonium bromide 0.3
[0083] The preparation method of the above-mentioned gallium indium tin alloy-manganese dioxide-titanium carbide MXene wave absorbing phase change composite particles is as follows:
[0084] 1) Polyvinyl pyrrolidone (PVP-K30) was dispersed in deionized water, and then the gallium indium tin alloy was added and intermittent ultrasonic dispersion was performed using an ultrasonic cell disruptor (ultrasonication for 2s, intermittent for 2s, and this cycle was repeated). The ultrasonic power was 200W, the ultrasonic dispersion time was 10min, and the mass ratio of gallium indium tin alloy, polyvinyl pyrrolidone, and deionized water was 1:0.1:20 to obtain a gallium indium tin alloy dispersion; potassium permanganate was added to the deionized water, and the mass ratio of potassium permanganate to deionized water was 1 :1600, mechanically stirred for 5 minutes at a stirring speed of 500 rpm, then added gallium indium tin alloy dispersion, the mass ratio of potassium permanganate to gallium indium tin alloy was 0.13:1, mechanically stirred for 30 minutes at a stirring speed of 500 rpm, then the product was alternately centrifuged 3 times and washed with water 3 times, the speed of the centrifuge was 2000 rpm, the time of a single centrifugation was 5 minutes, and then the solid obtained by centrifugation was freeze-dried at -50°C for 12 hours to obtain gallium indium tin alloy-manganese dioxide composite particles;
[0085] 2) adding the gallium indium tin alloy-manganese dioxide composite particles to a hexadecyltrimethylammonium bromide aqueous solution, wherein the mass ratio of the gallium indium tin alloy-manganese dioxide composite particles, the hexadecyltrimethylammonium bromide, and water is 1:0.2:100, and then ultrasonically dispersing for 60 minutes, the ultrasonic power is 250 W, and then the product is alternately centrifuged 3 times and washed 3 times, the speed of the centrifuge is 2000 rpm, and the single centrifugation time is 5 minutes, to obtain surface-modified gallium indium tin alloy-manganese dioxide composite particles;
[0086] 3) Add titanium carbide MXene to deionized water, ultrasonically disperse for 60 minutes, the ultrasonic power is 250 W, and then add surface modified gallium indium tin alloy-manganese dioxide composite particles, the mass ratio of surface modified gallium indium tin alloy-manganese dioxide composite particles, titanium carbide MXene, and deionized water is 1:0.07:100, mechanically stir for 10 hours, the stirring speed is 500 rpm, centrifuge for 5 minutes, the speed of the centrifuge is 2000 rpm, and then the solid obtained by centrifugation is placed at -50°C and freeze-dried for 24 hours to obtain gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particles.
[0087] Embodiment 4:
[0088] A gallium indium tin alloy-manganese dioxide-titanium carbide MXene wave absorbing phase change composite particle, which is composed of a gallium indium tin alloy core, a manganese dioxide intermediate shell layer and a titanium carbide MXene outer coating layer. The specific components and contents are shown in the following table:
[0089] Table 4 Composition of a gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particle
[0090]
[0091]
[0092] The preparation method of the above-mentioned gallium indium tin alloy-manganese dioxide-titanium carbide MXene wave absorbing phase change composite particles is as follows:
[0093] 1) Polyvinyl pyrrolidone (PVP-K30) was dispersed in deionized water, and then the gallium indium tin alloy was added and intermittent ultrasonic dispersion was performed using an ultrasonic cell disruptor (ultrasonication for 2s, intermittent for 2s, and this cycle was repeated). The ultrasonic power was 350W, the ultrasonic dispersion time was 10min, and the mass ratio of gallium indium tin alloy, polyvinyl pyrrolidone, and deionized water was 1:0.1:20 to obtain a gallium indium tin alloy dispersion; potassium permanganate was added to the deionized water, and the mass ratio of potassium permanganate to deionized water was 1 :1600, mechanically stirred for 5 minutes at a stirring speed of 500 rpm, then added gallium indium tin alloy dispersion, the mass ratio of potassium permanganate to gallium indium tin alloy was 0.13:1, mechanically stirred for 30 minutes at a stirring speed of 500 rpm, then the product was alternately centrifuged 3 times and washed with water 3 times, the speed of the centrifuge was 2000 rpm, the time of a single centrifugation was 5 minutes, and then the solid obtained by centrifugation was freeze-dried at -50°C for 12 hours to obtain gallium indium tin alloy-manganese dioxide composite particles;
[0094] 2) adding the gallium indium tin alloy-manganese dioxide composite particles to a hexadecyltrimethylammonium bromide aqueous solution, wherein the mass ratio of the gallium indium tin alloy-manganese dioxide composite particles, the hexadecyltrimethylammonium bromide, and water is 1:0.2:100, and then ultrasonically dispersing for 60 minutes, the ultrasonic power is 250 W, and then the product is alternately centrifuged 3 times and washed 3 times, the speed of the centrifuge is 2000 rpm, and the single centrifugation time is 5 minutes, to obtain surface-modified gallium indium tin alloy-manganese dioxide composite particles;
[0095] 3) Add titanium carbide MXene to deionized water, ultrasonically disperse for 60 minutes, the ultrasonic power is 250 W, and then add surface modified gallium indium tin alloy-manganese dioxide composite particles, the mass ratio of surface modified gallium indium tin alloy-manganese dioxide composite particles, titanium carbide MXene, and deionized water is 1:0.1:100, mechanically stir for 10 hours, the stirring speed is 500 rpm, centrifuge for 5 minutes, the speed of the centrifuge is 2000 rpm, and then the solid obtained by centrifugation is placed at -50°C and freeze-dried for 24 hours to obtain gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particles.
[0096] Embodiment 5:
[0097] A gallium indium tin alloy-manganese dioxide-titanium carbide MXene wave absorbing phase change composite particle, which is composed of a gallium indium tin alloy core, a manganese dioxide intermediate shell layer and a titanium carbide MXene outer coating layer. The specific components and contents are shown in the following table:
[0098] Table 5 Composition of a gallium indium tin alloy-manganese dioxide-titanium carbide MXene microwave absorbing phase change composite particle
[0099]
[0100]
[0101] The preparation method of the above-mentioned gallium indium tin alloy-manganese dioxide-titanium carbide MXene wave absorbing phase change composite particles is as follows:
[0102] 1) Polyvinyl pyrrolidone (PVP-K30) was dispersed in deionized water, and then the gallium indium tin alloy was added and intermittent ultrasonic dispersion was performed using an ultrasonic cell disruptor (ultrasonication for 2s, intermittent for 2s, and this cycle was repeated). The ultrasonic power was 200W, the ultrasonic dispersion time was 10min, and the mass ratio of gallium indium tin alloy, polyvinyl pyrrolidone, and deionized water was 1:0.1:20 to obtain a gallium indium tin alloy dispersion; potassium permanganate was added to the deionized water, and the mass ratio of potassium permanganate to deionized water was 1 :1600, mechanically stirred for 5 minutes at a stirring speed of 500 rpm, then added gallium indium tin alloy dispersion, the mass ratio of potassium permanganate to gallium indium tin alloy was 0.32:1, mechanically stirred for 30 minutes at a stirring speed of 500 rpm, then the product was alternately centrifuged 3 times and washed with water 3 times, the speed of the centrifuge was 2000 rpm, the time of a single centrifugation was 5 minutes, and then the solid obtained by centrifugation was freeze-dried at -50°C for 12 hours to obtain gallium indium tin alloy-manganese dioxide composite particles;
[0103] 2) adding the gallium indium tin alloy-manganese dioxide composite particles to a hexadecyltrimethylammonium bromide aqueous solution, wherein the mass ratio of the gallium indium tin alloy-manganese dioxide composite particles, the hexadecyltrimethylammonium bromide, and water is 1:0.2:100, and then ultrasonically dispersing for 60 minutes, the ultrasonic power is 250 W, and then the product is alternately centrifuged 3 times and washed 3 times, the speed of the centrifuge is 2000 rpm, and the single centrifugation time is 5 minutes, to obtain surface-modified gallium indium tin alloy-manganese dioxide composite particles;
[0104] 3) Add titanium carbide MXene to deionized water, ultrasonically disperse for 60 minutes, the ultrasonic power is 250 W, and then add surface modified gallium indium tin alloy-manganese dioxide composite particles, the mass ratio of surface modified gallium indium tin alloy-manganese dioxide composite particles, titanium carbide MXene, and deionized water is 1:0.1:100, mechanically stir for 10 hours, the stirring speed is 500 rpm, centrifuge for 5 minutes, the speed of the centrifuge is 2000 rpm, and then the solid obtained by centrifugation is placed at -50°C and freeze-dried for 24 hours to obtain gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particles.
[0105] Comparative Example 1:
[0106] A gallium indium tin alloy-manganese dioxide composite particle, which is composed of a gallium indium tin alloy core and a manganese dioxide shell. The specific components and contents are shown in the following table:
[0107] Table 6 Composition of a gallium indium tin alloy-manganese dioxide composite particle
[0108]
[0109]
[0110] The preparation method of the above-mentioned gallium indium tin alloy-manganese dioxide composite particles is as follows:
[0111] Polyvinyl pyrrolidone (PVP-K30) was dispersed in deionized water, and then the gallium indium tin alloy was added and intermittent ultrasonic dispersion was performed using an ultrasonic cell disruptor (ultrasonication for 2s, intermittent for 2s, and this cycle was repeated). The ultrasonic power was 200W, the ultrasonic dispersion time was 10min, and the mass ratio of the gallium indium tin alloy, polyvinyl pyrrolidone, and deionized water was 1:0.1:20 to obtain a gallium indium tin alloy dispersion. Potassium permanganate was added to the deionized water, and the mass ratio of potassium permanganate to deionized water was 1: 1600, mechanically stirred for 5 minutes at a stirring speed of 500 rpm, then added gallium indium tin alloy dispersion, the mass ratio of potassium permanganate to gallium indium tin alloy was 0.13:1, mechanically stirred for 30 minutes at a stirring speed of 500 rpm, and then the product was alternately centrifuged 3 times and washed with water 3 times, the speed of the centrifuge was 2000 rpm, the time of a single centrifugation was 5 minutes, and then the solid obtained by centrifugation was freeze-dried at -50°C for 12 hours to obtain gallium indium tin alloy-manganese dioxide composite particles.
[0112] Comparative Example 2:
[0113] A gallium indium tin alloy-titanium carbide MXene composite particle, which is composed of a gallium indium tin alloy core and a titanium carbide MXene coating layer. The specific components and contents are shown in the following table:
[0114] Table 7 Composition of a gallium indium tin alloy-titanium carbide MXene composite particle
[0115] Components Mass percentage (%) Gallium indium tin alloy (same as Example 1) 88.8 Titanium Carbide MXene 11 Hexadecyltrimethylammonium bromide 0.2
[0116] The preparation method of the above-mentioned gallium indium tin alloy-titanium carbide MXene composite particles is as follows:
[0117] 1) dispersing hexadecyltrimethylammonium bromide in deionized water, adding gallium indium tin alloy, and performing intermittent ultrasonic dispersion using an ultrasonic cell disruptor (ultrasonication for 2 seconds, intermittent for 2 seconds, and so on), the ultrasonic power is 200 W, the ultrasonic dispersion time is 10 minutes, the mass ratio of gallium indium tin alloy, hexadecyltrimethylammonium bromide, and deionized water is 1:0.1:20, and a gallium indium tin alloy dispersion is obtained, and then the product is alternately centrifuged 3 times and washed 3 times, the speed of the centrifuge is 2000 rpm, and the single centrifugation time is 5 minutes, to obtain surface-modified gallium indium tin alloy particles;
[0118] 2) Add titanium carbide MXene to deionized water, ultrasonically disperse for 60 minutes, the ultrasonic power is 250 W, and then add surface modified gallium indium tin alloy particles, the mass ratio of surface modified gallium indium tin alloy particles, titanium carbide MXene, and deionized water is 1:0.1:100, mechanically stir for 10 hours, the stirring speed is 500 rpm, centrifuge for 5 minutes, the speed of the centrifuge is 2000 rpm, and then the solid obtained by centrifugation is placed at -50 ° C and freeze-dried for 24 hours to obtain gallium indium tin alloy-titanium carbide MXene composite particles.
[0119] Performance Test:
[0120] The gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particles in Examples 1 to 5, the gallium indium tin alloy-manganese dioxide composite particles in Comparative Example 1, and the gallium indium tin alloy-titanium carbide MXene composite particles in Comparative Example 2 were respectively mixed with paraffin in a mass ratio of 1:1, and then pressed into coaxial rings with an outer diameter of 7 mm and an inner diameter of 3.04 mm. The coaxial method was used to test the absorbing performance, and the differential thermal analyzer (DSC) of NETZSCH of Germany was used to test the phase change latent heat of the composite particles in Examples 1 to 5, Comparative Example 1 and Comparative Example 2 (the heating rate was 10°C / min, and the temperature range was -40°C to 150°C). The absorbing performance of the coaxial ring sample finally obtained (the reflection loss of the coaxial ring sample varies with the frequency as shown in the curve) was Figure 4 The phase change latent heat test results of the composite particles are shown in the following table:
[0121] Table 8 Wave absorption performance of coaxial ring samples and phase change latent heat test results of composite particles
[0122]
[0123] From Table 8 and Figure 4 It can be seen that:
[0124] 1) The gallium indium tin alloy-manganese dioxide-titanium carbide MXene absorbing phase change composite particles in Examples 1 to 5 (having a unique three-layer core-shell structure) have better absorbing performance than the gallium indium tin alloy-manganese dioxide composite particles in Comparative Example 1 (double-layer core-shell structure) and the gallium indium tin alloy-titanium carbide MXene composite particles in Comparative Example 2 (double-layer core-shell structure). The reason is that the manganese dioxide shell layer improves the impedance mismatch phenomenon of the composite of gallium indium tin alloy and titanium carbide MXene, and at the same time brings more heterogeneous interfaces, increases the interface polarization loss, and thus improves the absorbing performance of the composite particles;
[0125] 2) In Examples 1 to 3, by adjusting the amount of titanium carbide MXene, the minimum reflection loss of the obtained absorbing phase change composite particles is slightly reduced, and the maximum effective absorption bandwidth is increased from 3.64 GHz (Example 1) to 4.32 GHz (Example 3), and the matching thickness is only 1.30 mm;
[0126] 3) In Examples 2 and 4-5, the absorbing performance of the absorbing phase change composite particles can also be adjusted by adjusting the thickness of the manganese dioxide shell layer. In Example 4, by increasing the ultrasonic power and reducing the particle size of the gallium indium tin alloy particles, the contact area between the gallium indium tin alloy particles and potassium permanganate is increased, and the thickness of the manganese dioxide shell layer in the absorbing phase change composite particles is reduced, so that the minimum reflection loss of the absorbing phase change composite particles is reduced from -47.43 dB to -51.12 dB;
[0127] 4) In Example 5, the thickness of the manganese dioxide shell in the absorbing phase change composite particles was increased by increasing the dosage of potassium permanganate, and the electromagnetic parameters of the absorbing phase change composite particles were adjusted, so that the minimum reflection loss of the absorbing phase change composite particles was reduced from -47.43 dB to -49.06 dB, and the maximum effective absorption bandwidth was 4.53 GHz;
[0128] In summary, the present invention can obtain liquid metal-manganese oxide-MXene absorbing phase change composite particles with different absorbing properties by adjusting the amount of MXene, the thickness of the manganese dioxide shell layer, etc.
[0129] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A liquid metal-manganese oxide-MXene wave absorbing phase change composite particle, characterized in that: The composition includes a liquid metal core, a manganese oxide intermediate shell and a MXene outer coating layer.
2. The liquid metal-manganese oxide-MXene wave absorbing phase change composite particles according to claim 1, characterized in that: The liquid metal-manganese oxide-MXene wave absorbing phase change composite particles include the following components in percentage by mass: Liquid metal: 57%~88%; Manganese oxide: 4% to 26%; MXene: 5% to 16%; Surfactant: 0.1%~1%.
3. The liquid metal-manganese oxide-MXene wave absorbing phase change composite particles according to claim 1 or 2, characterized in that: The liquid metal is at least one of single substance gallium, gallium-indium alloy, gallium-indium-tin alloy and gallium-zinc alloy.
4. The liquid metal-manganese oxide-MXene wave absorbing phase change composite particle according to claim 1 or 2, characterized in that: The manganese oxide is at least one of manganese dioxide, trimanganese tetroxide and dimanganese trioxide.
5. The liquid metal-manganese oxide-MXene wave absorbing phase change composite particle according to claim 1 or 2, characterized in that: The MXene is at least one of titanium carbide MXene, manganese carbide MXene, and zirconium carbide MXene.
6. The liquid metal-manganese oxide-MXene wave absorbing phase change composite particle according to claim 2, characterized in that: The surfactant is at least one of polyvinyl pyrrolidone, cetyl trimethyl ammonium bromide, cetyl trimethyl ammonium chloride and cetyl pyridine.
7. A method for preparing liquid metal-manganese oxide-MXene wave absorbing phase change composite particles according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) dispersing liquid metal and surfactant in water to prepare a liquid metal dispersion, then adding the dispersion into a potassium permanganate solution for reaction, and then separating and purifying the product to obtain liquid metal-manganese oxide composite particles; 2) dispersing the liquid metal-manganese oxide composite particles and the surfactant in water to perform surface modification of the liquid metal-manganese oxide composite particles, and then separating and purifying the products to obtain surface-modified liquid metal-manganese oxide composite particles; 3) Dispersing MXene in water to prepare a MXene dispersion, then adding the surface-modified liquid metal-manganese oxide composite particles into the MXene dispersion to electrostatically adsorb and coat the MXene on the surface of the surface-modified liquid metal-manganese oxide composite particles, and then separating and purifying the products to obtain liquid metal-manganese oxide-MXene absorbing phase change composite particles.
8. The preparation method according to claim 7, characterized in that: In step 1), the mass ratio of the liquid metal to potassium permanganate is 1:0.10-0.63; in step 3), the mass ratio of the surface-modified liquid metal-manganese oxide composite particles to MXene is 1:0.05-0.
20.
9. The preparation method according to claim 7 or 8, characterized in that: The reaction in step 1) is carried out at room temperature for 10 to 60 minutes; and the electrostatic adsorption coating in step 3) is carried out at room temperature for 6 to 12 hours.
10. An application of the liquid metal-manganese oxide-MXene absorbing phase change composite particles as described in any one of claims 1 to 6 in the field of 5G communications, consumer electronics or national defense and military industry.
Citation Information
Patent Citations
Ferrite-manganese oxide-MXene composite wave-absorbing particle as well as preparation method and application thereof
CN114552231A
Flexible ultrathin electromagnetic shielding and heat conducting difunctional composite film and preparation method thereof
CN118085562A
Cited By
Manufacturing method of silicon carbide nanowire enhanced gallium indium liquid metal composite graphene oxide ultralight electromagnetic absorption aerogel
CN120248411A
High-performance composite wave-absorbing material as well as preparation method and application thereof
CN120824556A
